2020
DOI: 10.1080/07853890.2020.1836566
|View full text |Cite
|
Sign up to set email alerts
|

Admission hyperglycaemia as a predictor of mortality in patients hospitalized with COVID-19 regardless of diabetes status: data from the Spanish SEMI-COVID-19 Registry

Abstract: Background Hyperglycaemia has emerged as an important risk factor for death in coronavirus disease 2019 (COVID-19). The aim of this study was to evaluate the association between blood glucose (BG) levels and in-hospital mortality in non-critically patients hospitalized with COVID-19. Methods This is a retrospective multi-centre study involving patients hospitalized in Spain. Patients were categorized into three groups according to admission BG levels: <140 mg/dL, 140–18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
102
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 25 publications
12
102
0
6
Order By: Relevance
“…The combination of the elevated biomarkers of systemic inflammation and lactate suggest a systemic inflammatory response leading to stress hyperglycemia in the group without pre-existing DM. Several studies in hospitalized individuals with COVID-19 have reported that hyperglycemia is associated with more severe infection, and adverse outcomes such as respiratory failure requiring mechanical ventilation, multi-organ failure, and death ( 8 , 16 ). Our findings are consistent with another retrospective study from North-East Italy, which showed that new-onset diabetes or admission hyperglycemia were predictors of more severe COVID-19, an association which was stronger among patients without pre-existing diabetes than those with a history of diabetes ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the elevated biomarkers of systemic inflammation and lactate suggest a systemic inflammatory response leading to stress hyperglycemia in the group without pre-existing DM. Several studies in hospitalized individuals with COVID-19 have reported that hyperglycemia is associated with more severe infection, and adverse outcomes such as respiratory failure requiring mechanical ventilation, multi-organ failure, and death ( 8 , 16 ). Our findings are consistent with another retrospective study from North-East Italy, which showed that new-onset diabetes or admission hyperglycemia were predictors of more severe COVID-19, an association which was stronger among patients without pre-existing diabetes than those with a history of diabetes ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have also associated hyperglycemia with worse outcomes in hospitalized patients with COVID-19 ( 5 , 6 , 7 ). However, these studies have analyzed these questions in hospitalized populations predominantly outside of the intensive-care unit (ICU), and the impact of hyperglycemia on mortality in critically ill patients with and without pre-existing DM in the setting of COVID-19 remains unclear ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Infection with coronaviridae may have repercussions in insulin secretion and glycemia [ 1 ]. Critically ill and non-critically ill patients with SARS-CoV-2 infection (Covid-19) may present with higher-than-expected glycemia, even in the absence of diabetes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Critically ill patients may show stress hyperglycemia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated Hemoglobin A1c levels has been associated with worse COVID-19 prognosis [4] . Hyperglycemia was also associated with requirement for mechanical ventilation, intensive care unit (ICU) admission and mortality [5] . After adjusting for age, diabetes, hypertension and other confounding factors, hyperglycemia was reported to be an independent risk factor of mortality: when >180 mg/dL (hazard ratio 1.50 [95% CI: 1.31–1.73]), when 140–180 mg/dL (hazard ratio 1.48 [95%CI: 1.29–1.70]) [5] .…”
mentioning
confidence: 99%
“…Hyperglycemia was also associated with requirement for mechanical ventilation, intensive care unit (ICU) admission and mortality [5] . After adjusting for age, diabetes, hypertension and other confounding factors, hyperglycemia was reported to be an independent risk factor of mortality: when >180 mg/dL (hazard ratio 1.50 [95% CI: 1.31–1.73]), when 140–180 mg/dL (hazard ratio 1.48 [95%CI: 1.29–1.70]) [5] . Patients with higher blood glucose levels have more severe symptoms associated with SARS-CoV-2 infection (weighted mean difference 2.21 [95% CI: 1.30–3.13, P < 0.001]) [6] .…”
mentioning
confidence: 99%